Impact of CLSI Breakpoint Changes on Microbiology Laboratories and Antimicrobial Stewardship Programs - Heil, Emily L. (J Clin Microbiol, 2016)
In 2010, the Clinical and Laboratory Standards Institute (CLSI) lowered the MIC breakpoints for many beta-lactam antibiotics to enhance detection of known resistance among Enterobacteriaceae. The decision to implement these new breakpoints, including the changes announced in both 2010 and 2014, can have a significant impact on both microbiology laboratories and antimicrobial stewardship programs. In this commentary, we discuss the changes and how implementation of these updated CLSI breakpoints requires partnership between antimicrobial stewardship programs and the microbiology laboratory, including data on the impact that the changes had on antibiotic usage at our own institution.